Inquisitionis Hispanicae Artes: The Arts of the Spanish Inquisition. Reginaldus Gonsalvius Montanus. A Critical Edition of the Sanctae Inquisitionis Hispanicae Artes aliquot (1567) with a Modern English Translation, edited by Marcos J. Herráiz Pareja... - Álvaro Cancela Cilleruelo (Hispania Sacra, 2023)
-